Green Accounting dan Kinerja Lingkungan: Bukti Empiris atau Sekadar Narasi Bisnis? - Ghina Saumalia; Rina Tjandrakirana (Teewan Journal Solutions, 2025)
Green accounting is an approach that integrates environmental aspects into traditional accounting practices. This study aims to prove whether companies that implement green accounting and environmental performance actually implement it or it is all just a company's business narrative. Through a systematic literature review of recent studies, it was found that although several studies show a positive relationship between green accounting and environmental performance, there are also indications that the implementation is often symbolic without any real impact on environmental performance. The results of this study indicate that there are still many companies that only use green accounting and environmental performance as a marketing tool or social legitimacy without any concrete efforts in improving the environment.